The Use of Regional Marketing in the Conduct of Regional Policy - Jánošová, Denisa; Jobczyk, Tomasz (Political Preferences, 2020)
The purpose of the article is to demonstrate the close relationship between regional development and territorial marketing, which based on the implementation of the marketing concept focuses on creating regional and local products and their effective positioning towards potential buyers. The presented thesis is a result of reflection on using regional marketing in creating regional policy, based on consideration of the specific features of the region which marketing specialists are supposed to know in order to create a marketing plan for the respective region. Further, the marketing plan may be used in the political strategy of regional development based on the satisfaction of the residents’ needs and their individual development. The care of politicians, who fulfil their functions following the election by the citizens, and the development of residents would coexist with the creation of regional development. The phenomena should be closely interrelated. When describing the interrelation from a scientific perspective, it must be said that synergy of the indicated types of activity depends on a series of facts and correlations which fall within various scientific domains. Therefore, there is a need for multidisciplinary approach. The authors of the article hypothesize that management of regional development should be supported by the professional use of regional marketing, taking into account the assumption that each organization should shape its impact system by analysing its needs, already used solutions and the needs of its stakeholders. The views expressed are based on the analysis of selected literature.